Analisis Penggunaan Aplikasi E-Peken pada UMKM di Kecamatan Pakal dalam Meningkatkan Penjualan - Puspitasari, Dian; Kirana, Nanda Wahyu Indah (IAI Nasional Laa Roiba Bogor, 2024)
The phenomenon of increasing digitalization in the small and medium business sector has encouraged SMEs to adopt various digital applications to enhance efficiency and sales. In the Kecamatan Pakal, the use of the E-Peken application by SMEs has become an intriguing topic for research, considering its potential benefits in boosting sales. Pemberdayaan dan Ketahanan Ekonomi Nang Suroboyo also known as E-Peken, is an online shopping platform launched by the Surabaya City Government and is considered a solution for local SMEs. Therefore, this study aims to analyze the impact of using the E-Peken application on increasing SME sales in the Pakal District. This research is based on the Technology Acceptance Model theory, which explains the concept of user behavior towards new information technology systems. The research method used is a descriptive qualitative method. Data in this study were collected through surveys and in-depth interviews with SME owners who use E-Peken. The results of the study show that the owners' perception of the E-Peken application significantly influences a positive attitude and intention to use E-Peken. Additionally, the level of digital literacy among SME owners also plays an important role in determining how effectively the E-Peken application can be used to increase sales.